High Prevalence of Asymptomatic Neurocysticercosis in an Endemic Rural Community in Peru. - Luz M Moyano; Seth E O'Neal; Viterbo Ayvar; Guillermo Gonzalvez; Ricardo Gamboa; Percy Vilchez; Silvia Rodriguez; Joe Reistetter; Victor C W Tsang; Robert H Gilman; Armando E Gonzalez; Hector H Garcia; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Neurocysticercosis is a common helminthic infection of the central nervous system and an important cause of adult-onset epilepsy in endemic countries. However, few studies have examined associations between neurologic symptoms, serology and radiographic findings on a community-level. METHODOLOGY:We conducted a population-based study of resident's ≥2 years old in a highly endemic village in Peru (pop. 454). We applied a 14 -question neurologic screening tool and evaluated serum for antibodies against Taenia solium cysticercosis using enzyme-linked immunoelectrotransfer blot (LLGP-EITB). We invited all residents ≥18 years old to have non-contrast computerized tomography (CT) of the head. PRINCIPAL FINDINGS:Of the 385 residents who provided serum samples, 142 (36.9%) were seropositive. Of the 256 residents who underwent CT scan, 48 (18.8%) had brain calcifications consistent with NCC; 8/48 (17.0%) reported a history of headache and/or seizures. Exposure to T. solium is very common in this endemic community where 1 out of 5 residents had brain calcifications. However, the vast majority of people with calcifications were asymptomatic. CONCLUSION:This study reports a high prevalence of NCC infection in an endemic community in Peru and confirms that a large proportion of apparently asymptomatic residents have brain calcifications that could provoke seizures in the future.